DNA of Theileria orientalis, T. equi and T. capreoli in stable flies (Stomoxys calcitrans) - Hornok, Sándor (Parasit Vectors, 2020)
BACKGROUND: From a veterinary-medical point of view, the stable fly, Stomoxys calcitrans, is perhaps the economically most important blood-sucking muscoid fly species (Diptera: Muscidae), owing to its worldwide occurrence, frequently high local abundance, direct harm caused to livestock, pet animals and humans, as well as its vector role. Considering the latter in the context of protozoan parasites, the stable fly is a mechanical vector of trypanosomes and Besnoitia besnoiti. However, its role as a vector of piroplasms appears to be seldom studied, despite old data suggesting mechanical transmission of babesiae by dipteran flies. METHODS: In this study 395 stable flies (and one Haematobia stimulans) were collected at a cattle farm with known history of bovine theileriosis, and at further nine, randomly chosen locations in Hungary. These flies were separated according to sex (30 of them also cut into two parts: the head with mouthparts and the thorax-abdomen), followed by individual DNA extraction, then screening for piroplasms by PCR and sequencing. RESULTS: In stable flies, Theileria orientalis and T. capreoli were identified at the cattle farm and T. equi was identified in three other locations. At the cattle farm, significantly more male stable flies carried piroplasm DNA than females. There was no significant difference between the ratio of PCR-positive flies between the stable (void of cattle for at least two hours) and the pen on the pasture with cattle at the time of sampling. Among dissected flies (29 S. calcitrans and 1 H. stimulans), exclusively the thoracic-abdominal parts were PCR-positive, whereas the head and mouthparts remained negative. CONCLUSIONS: Theileria DNA is detectable in stable flies, in the case of T. orientalis at least for two hours after blood-feeding, and in the case of T. capreoli also in the absence of infected hosts (i.e. roe deer). Male flies rather than females, and thoracic-abdominal (most likely crop) contents rather than mouthparts may pose a risk of mechanical transmission. These data suggest that it is worth to study further the vector role of stable flies in the epidemiology of theilerioses, in which not the immediate, but rather the delayed type transmission seems possible. [Image: see text]